Tumpang Tindih Konflik Pada Struktur Naratif Novel Lelaki Harimau Karya Eka Kurniawan - Emi Asmida (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2020)
This research aims to reveal the overlapping conflicts in Eka Kurniawan’s Lekaki Harimau by applying Gerard Genette’s narrative theory. Conflicts in this research were affected by narrative structure in this text, however, this research focused on analyzing dominant narrative elements found in this novel, such as order, frequency, focalization, and voice. Qualitative method is used in this research by applying in-depth reading (close reading) to expose any conflicts acquired in dominant narrative elements. The results of this study indicate that the central conflict in this story is a murder conflict which was carried out by others conflicts. This conflict originated from the overlapping conflicts experienced by the main character and the other member of his family, those are: (1) domestic violence, (2) emotional affection, and (3) hatred conflict which involved acts of revenge. By discovering the finding from the analysis of overlapping conflicts, it revealed a criticism of the social condition in society about shaping the behavior of an individual which could be influenced by the smallest institutional system in the society called ‘family’. In another sense, the family has an important role in forming attitudes and behavior toward each individual.